(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The Great Indian Revolution of 1857 inspired the subsequent nationalistic movement, especially the revolutionary movement to liberate the motherland from the yoke of oppressive and exploitative alien rule. The revolutionary movement in India during the early decades of the 20th century was mainly confined to Bengal, Maharashtra and Punjab, but it first gained significant traction in Bengal with the formation of secret societies like Anushilan Samity and Jugantar. Among the various eminent Bengali revolutionaries was Jatindra Nath Mukherjee, who gave up his all, including his life, for the freedom of his country, but has not been accorded his due place in the annals of Indian historiographical accounts. Even though there is no dearth of historical documents related to him, he remains largely obscure beyond Bengal and Orissa. This Paper is an attempt to delve deep into the history and to bring to the fore the role played by this braveheart in the history of the Indian revolutionary movement, which forms a key stream in the river of the Indian freedom struggle.